The Influence of Online Game Mobile Legends in Students’ Vocabulary Mastery at Eleventh Grade of Vocational High School Number 1 Jambi City - M. Rhodiwa Adha; Suyadi Suyadi; Siti Aisyah (JELT: Journal of English Language Teaching, 2022)
The objectives of this research is to find out what is the influence of online game Mobile Legends in students’ vocabulary mastery at eleventh grade of Vocational High School Number 1 Kota Jambi. This research has done this research while Covid-19 Pandemic and did this research face to face with students. This research used quantitative method with a survey design. In this research, population of this research is students of Eleventh Grade at Vocational High School Kota Jambi and sample of the research is XI TKJ 3 class. This research used a questionnaire as a collecting data consists of 16 questions divided into positive influence, negative influence and related vocabulary mastery. This research used descriptive analysis as the analyzing data. The results of this research showed that positive influence has a higher score 654 (44,18%) than negative influence has a lower score 416 (28,07%). And, in related vocabulary mastery got score 413 (27,86%). It could be concluded that Mobile Legends have greater positive influence than negative influence in learning English, especially in mastering English vocabulary such as the students can add new English vocabulary by playing the game and they can also practice other English skills like listening, writing, reading, and speaking.